An unladylike secret - Murray, Amita (Murray, Amita. Marleigh sisters novel., 2025)
"Mira Marleigh, as far as the public is concerned, is an unassuming companion. She quietly drifts through London society accompanying her dear friend and confidant, Ursula. Mira flies under the radar, which is exactly how she likes it, because unbeknownst to everyone besides her sisters and Ursula, she is the anonymous author of one of the most popular society circulars under the pseudonym Aurelius. As a purveyor of society gossip, keeping a low profile allows her to see and hear nearly everything. But is this prosaic, passionless persona that she has carefully constructed really who Mira wants to be? When one of her circulars detailing a heated argument between the blue-blooded brothers Stephen and Finnegan Underwood ends up as the basis for the case against Finnegan when Stephen turns up dead not two days later, Stephen's widow, Lucretia, is desperate for Aurelius's help in proving Finnegan innocent. So, acting as Aurelius's "assistant," Mira travels to the coastal town of Devonshire where she agrees to help the young widow."--